2003
DOI: 10.1179/136217103225009125
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of DH36 steel

Abstract: Hot rolled DH36 carbon steel, 6 . 4 mm in thickness, was friction stir welded at speeds of 3 . 4 mm s 2 1 (8 in min 2 1 ), 5 . 1 mm s 2 1 (12 in min 2 1 ), and 7 . 6 mm s 2 1 (18 in min 2 1 ). Single pass welds free of volumetric defects were produced at each speed. The relationships between welding parameters and weld properties are discussed. Optical microscopy, microhardness testing, and transverse and longitudinal tensile tests have been performed. Bainite and martensite are found in the nugget region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 5 publications
9
106
0
3
Order By: Relevance
“…It is noted that the peak temperatures at the 400 mm/min welding speed are all below 700°C for all the carbon steels, which are all below A 1 , and therefore, the transformations does not occur. It can be stated that the temperatures, much lower than the peak temperatures reported in previous papers, 9,10) were controlled in this study. On the other hand, by controlling the welding conditions (e.g., increasing the rotation speed or decreasing the welding speed), the temperature can exceed the A 1 or A 3 temperature, and therefore, the welding can be performed in the ferrite-austenite two-phase region or austenite single-phase region, and the transformation then produces various microstructures due to the different cooling rates after welding.…”
Section: Temperature Cyclementioning
confidence: 67%
See 1 more Smart Citation
“…It is noted that the peak temperatures at the 400 mm/min welding speed are all below 700°C for all the carbon steels, which are all below A 1 , and therefore, the transformations does not occur. It can be stated that the temperatures, much lower than the peak temperatures reported in previous papers, 9,10) were controlled in this study. On the other hand, by controlling the welding conditions (e.g., increasing the rotation speed or decreasing the welding speed), the temperature can exceed the A 1 or A 3 temperature, and therefore, the welding can be performed in the ferrite-austenite two-phase region or austenite single-phase region, and the transformation then produces various microstructures due to the different cooling rates after welding.…”
Section: Temperature Cyclementioning
confidence: 67%
“…[2][3][4] After the initial trial for the higher temperature materials was successful by Thomas et al,5) several previous studies have reported the friction stir welding of interstitial free steel (IF steel: 20 ppm C), [6][7][8] carbon steels, [9][10][11][12][13][14][15] alloy steels, 16) and stainless steels. [17][18][19][20][21][22] Lienert et al 9) and Reynolds et al 10) studied one kind of carbon steel-the 1018 steel (0.18%C-0.01%Si-0.82%Mn-0.011%P-0.006%S) and a C-Mn steel (0.18%C-0.10-0.50%Si-0.9-1.6%Mn-0.035%P-0.035 %S) respectively. They reported that the FSW achieves grain refinement in the stir zone of the carbon steel, similar to Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…2.2.1 페라이트계 강 페라이트계 강에 대한 FSW 보고는 지금 까지 연강 8) , 각종 탄소강 [9][10][11][12][13][14] , DH36강 15) , C-Mn강 16,17) , 라인 파이 프용강 18,19) , 12%Cr강 20,21) , HSLA-65강 [22][23][24][25][26] , DP강 [27][28][29][30] , B첨가강 . 그러나 접합조건을 조절하여 냉 각속도 및 최고도달온도를 제어하면 FSW후 경화조직 의 형성을 억제할 수 있다 [10][11] .…”
Section: 철강재 Fsw접합부 특성unclassified
“…A comparison between FSW and submerged arc welding (SAW) of DH36 showed microstructure and mechanical properties improved as a [3]. Advantages of FSW of DH36 steel were also studied [4] by relating welding parameters to mechanical properties. Defects associated with FSW of DH36 steel were reported by Stevenson et al [5] and classified into five groups, namely lower embedded, upper embedded, incomplete fusion, connectivity flaw, and root flaw.…”
Section: Introductionmentioning
confidence: 99%